Strength Analysis of High-speed EMUs Equipment Cabin under Influence of Aerodynamic Loads - Huadong DUAN; Dianxi XIAO; Wenhui YUAN (机车电传动)
By comparing and analyzing the existing strength calculation and evaluation criteria of equipment cabin of high-speed EMUs, the method of setting aerodynamic load as fixed value to study the fatigue strength of equipment compartment was put forward. Through static strength analysis and optimization, the structure of equipment cabin was improved, and the effects of pneumatic and impact separately and simultaneously on the static load performance of equipment cabin were compared and analyzed. At the same time, the fatigue characteristics of equipment cabin under different aerodynamic loads were explored according to the standard and measured loads. The analysis results show that the aerodynamic load has a great influence on the strength of the equipment cabin, and the fatigue strength of the equipment cabin meets the design requirements under (±1 500 Pa) aerodynamic load.